The LRRK2 G2385R variant is a partial loss-of-function mutation that affects synaptic vesicle trafficking through altered protein interactions - Maria Dolores Perez Carrion (Nature Portfolio, 2017)
Abstract Mutations in the Leucine-rich repeat kinase 2 gene (LRRK2) are associated with familial Parkinson’s disease (PD). LRRK2 protein contains several functional domains, including protein-protein interaction domains at its N- and C-termini. In this study, we analyzed the functional features attributed to LRRK2 by its N- and C-terminal domains. We combined TIRF microscopy and synaptopHluorin assay to visualize synaptic vesicle trafficking. We found that N- and C-terminal domains have opposite impact on synaptic vesicle dynamics. Biochemical analysis demonstrated that different proteins are bound at the two extremities, namely β3-Cav2.1 at N-terminus part and β-Actin and Synapsin I at C-terminus domain. A sequence variant (G2385R) harboured within the C-terminal WD40 domain increases the risk for PD. Complementary biochemical and imaging approaches revealed that the G2385R variant alters strength and quality of LRRK2 interactions and increases fusion of synaptic vesicles. Our data suggest that the G2385R variant behaves like a loss-of-function mutation that mimics activity-driven events. Impaired scaffolding capabilities of mutant LRRK2 resulting in perturbed vesicular trafficking may arise as a common pathophysiological denominator through which different LRRK2 pathological mutations cause disease.